Thyroid hormone resistance syndrome due to mutations in the thyroid hormone receptor α gene (THRA). Issue 5 (10th February 2015) - Tylki-Szymańska, Anna; Acuna-Hidalgo, Rocio; Krajewska-Walasek, Małgorzata; Lecka-Ambroziak, Agnieszka; Steehouwer, Marloes; Gilissen, Christian; Brunner, Han G; Jurecka, Agnieszka; Różdżyńska-Świątkowska, Agnieszka; Hoischen, Alexander; Chrzanowska, Krystyna H
Abstract : Background: Resistance to thyroid hormone is characterised by a lack of response of peripheral tissues to the active form of thyroid hormone (triiodothyronine, T3). In about 85% of cases, a mutation in THRB, the gene coding for thyroid receptor β (TRβ), is the cause of this disorder. Recently, individual reports described the first patients with thyroid hormone receptor α gene ( THRA ) defects. Methods: We used longitudinal clinical assessments over a period of 18 years at one hospital setting combined with biochemical and molecular studies to characterise a novel thyroid hormone resistance syndrome in a cohort of six patients from five families. Findings: Using whole exome sequencing and subsequent Sanger sequencing, we identified truncating and missense mutations in the THRA gene in five of six individuals and describe a distinct and consistent phenotype of mild hypothyroidism (growth retardation, relatively high birth length and weight, mild-to-moderate mental retardation, mild skeletal dysplasia and constipation), specific facial features (round, somewhat coarse and flat face) and macrocephaly. Laboratory investigations revealed anaemia and slightly elevated cholesterol, while the thyroid profile showed low free thyroxine (fT4) levels coupled with high free T3 (fT3), leading to an altered T4 : T3 ratio, along with normal thyroid-stimulating hormone levels. We observed a genotype–phenotype correlation, with milder outcomes for missense mutations and more severe phenotypical effects for truncating mutations. Interpretation: THRA mutations may be more common than expected. In patients with clinical symptoms of mild hypothyreosis without confirmation in endocrine studies, a molecular study of THRA defects is strongly recommended.